On Convergence in Norm of Functions in L^p Spaces by Convolution Using Dilation Kernel - Herlinawati, Elin (Jurnal Matematika, Statistika dan Komputasi, 2025)
In this paper, we investigate the convergence in norm of functions in L^p (R^d) by convolution. We use dilation kernel from L^1 as approximation identity and prove convergence of a function using convolution with dilation kernel in norm ‖∙‖_p for 1≤p<∞ and norm ‖∙‖_∞ for p=∞.